The Effect Of Knowledge And Risk On Investment Interest Among Students At Dehasen University, Bengkulu - Wiranda Buaton; Karona Cahya Susena; Wagini Wagini (Utami Publisher, 2026)
This study aims to determine and analyze the influence of knowledge and risk on investment interest among students at Dehasen University Bengkulu. Knowledge is considered an important factor that shapes students' understanding of investment concepts, benefits, and mechanisms, including the various forms of risk involved. On the other hand, perceptions of risk also determine students' readiness to make investment decisions. This study involved 106 students from the 2022 Management Study Program as samples, with data obtained through a questionnaire. The analysis was conducted using multiple linear regression, determination test, as well as t-test and F-test as hypothesis testing. The regression analysis resulted in the equation Y = 4.023 + 0.484X1 + 0.395X2, which shows that knowledge (X1) and risk (X2) have a positive effect on investment interest (Y). The coefficient of determination of 0.768 indicates that knowledge and risk can explain 76.8% of the variation in student investment interest, while the remaining 23.2% is influenced by other variables outside the study. The t-test results at a significance level of 0.05 show that knowledge and risk have a significant partial effect, while the F-test confirms that both variables simultaneously have a significant effect on the investment interest of Dehasen Bengkulu University students. Overall, these findings confirm that increasing knowledge and understanding of risk can encourage students to invest more.”